Genetic polymorphisms in the renin-angiotensin-aldosterone system associated with expression of left ventricular hypertrophy in hypertrophic cardiomyopathy: a study of five polymorphic genes in a family with a disease causing mutation in the myosin binding protein C gene. Issue 3 (1st March 2002) - Ortlepp, J R; Vosberg, H P; Reith, S; Ohme, F; Mahon, N G; Schröder, D; Klues, H G; Hanrath, P; McKenna, W J
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is an inherited disease of the sarcomere characterised clinically by myocardial hypertrophy and its consequences. Phenotypic expression is heterogeneous even within families with the same aetiological mutation and may be influenced by additional genetic factors. Objective: To determine the influence of genetic polymorphisms of the renin-angiotensin-aldosterone system (RAAS) on ECG and two dimensional echocardiographic left ventricular hypertrophy (LVH) in genetically identical patients with HCM. Patients and methods: Polymorphisms of five RAAS components were determined in 26 gene carriers from a single family with HCM caused by a previously identified myosin binding protein C mutation. Genotypes associated with a higher activation status of the RAAS were labelled "pro-LVH genotypes". Results: There was a non-biased distribution of pro-LVH genotypes in the gene carriers. Those without pro-LVH genotypes did not manifest cardiac hypertrophy whereas gene carriers with pro-LVH genotypes did (mean (SD) left ventricular muscle mass 190 (48) v 320 (113), p = 0.002; interventricular septal thickness 11.5 (2.0) v 16.4 (6.7), p = 0.01; pathological ECG 0% (0 of 10) v 63% (10 of 16), respectively). Multivariate analysis controlling for age, sex, and hypertension confirmed an independent association between the presence of pro-LVH polymorphisms and left ventricular mass. When each polymorphism was assessed individually, carriers of each pro-LVH genotype had a significantly greater left ventricular mass than those with no pro-LVH mutation; these associations, with the exception of cardiac chymase A AA polymorphism (p = 0.06), remained significant in multivariate analysis. Conclusion: Genetic polymorphisms of the RAAS influence penetrance and degree of LVH in 26 gene carriers from one family with HCM caused by a myosin binding protein C mutation.